Securing a place for reading in composition: the importance of teaching for transfer - Carillo, Ellen C., author; Utah State University Press, publisher (Colorado State University. Libraries, 2015)
Securing a Place for Reading in Composition addresses the dissonance between the need to prepare students to read, not just write, complex texts and the lack of recent scholarship on reading-writing connections. Author Ellen C. Carillo argues that including attention-to-reading practices is crucial for developing more comprehensive literacy pedagogies. Students who can read actively and reflectively will be able to work successfully with the range of complex texts they will encounter throughout their post-secondary academic careers and beyond. Considering the role of reading within composition.
1. Introduction -- 2. Reading in Contemporary First-Year Composition Classes -- 3. Historical Contexts -- 4. Reading in Composition Research and Teaching, 1980-1993 -- 5. Transfer of Learning Scholarship and Reading Instruction in First-Year Composition -- 6. Teaching Mindful Reading to Promote the Transfer of Reading Knowledge -- 7. Epilogue: A Changing Landscape; Appendix A: Annotated Bibliography -- Appendix B: Handouts from Professional Development Workshops on Integrating Attention to Reading into Courses across the Curriculum -- Appendix C: Supporting Materials from National Survey of First-Year Composition Instructors and Their Students.
Keywords: Composition (Language arts); Reading; English language -- Rhetoric -- Study and teaching